2017
DOI: 10.1002/hbm.23833
|View full text |Cite
|
Sign up to set email alerts
|

A multisample study of longitudinal changes in brain network architecture in 4–13‐year‐old children

Abstract: Recent advances in human neuroimaging research have revealed that white-matter connectivity can be described in terms of an integrated network, which is the basis of the human connectome. However, the developmental changes of this connectome in childhood are not well understood. This study made use of two independent longitudinal diffusion-weighted imaging data sets to characterize developmental changes in the connectome by estimating age-related changes in fractional anisotropy (FA) for reconstructed fibers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 85 publications
3
28
0
Order By: Relevance
“…A recent study replicated and extended these findings in two independent longitudinal datasets with participants ranging from ages 4 to 13 years (Wierenga, van den Heuvel, et al 2018). As observed in Baker et al, 2015, the hub regions of the brain showed the most substantial changes in connectivity between childhood and early adolescence (Wierenga, van den Heuvel, et al 2018). Further, this study found that white matter tracts connecting distal regions of the brain demonstrated larger developmental changes in FA than white matter tracts connecting proximal brain regions (Wierenga, van den Heuvel, et al 2018).…”
Section: White Matter Microstructuresupporting
confidence: 56%
See 2 more Smart Citations
“…A recent study replicated and extended these findings in two independent longitudinal datasets with participants ranging from ages 4 to 13 years (Wierenga, van den Heuvel, et al 2018). As observed in Baker et al, 2015, the hub regions of the brain showed the most substantial changes in connectivity between childhood and early adolescence (Wierenga, van den Heuvel, et al 2018). Further, this study found that white matter tracts connecting distal regions of the brain demonstrated larger developmental changes in FA than white matter tracts connecting proximal brain regions (Wierenga, van den Heuvel, et al 2018).…”
Section: White Matter Microstructuresupporting
confidence: 56%
“…Specifically, connections between subcortical hubs decreased across late adolescence and connections between frontal-subcortical and frontalparietal hubs increased across late adolescence (Baker et al 2015). A recent study replicated and extended these findings in two independent longitudinal datasets with participants ranging from ages 4 to 13 years (Wierenga, van den Heuvel, et al 2018). As observed in Baker et al, 2015, the hub regions of the brain showed the most substantial changes in connectivity between childhood and early adolescence (Wierenga, van den Heuvel, et al 2018).…”
Section: White Matter Microstructurementioning
confidence: 63%
See 1 more Smart Citation
“…Frontal regions undergo a great deal of development and establishment of connections during childhood (Sowell et al, ; Wierenga et al, ; Wierenga et al, ), consistent with frontal hub changes noted in healthy control children during periods of increased demand, such as in the early school years. Hubs are highly connected regions globally that direct the flow of information in brain networks.…”
Section: Discussionmentioning
confidence: 60%
“…Intercept and age were fixed effects, while within participant dependence ( d p ) was modelled as a random effect. This same procedure was used in other longitudinal studies that explored brain connectivity changes over time (Wierenga et al, ). The linear mixed model included the 32 participants who had valid data for at least two visits.…”
Section: Methodsmentioning
confidence: 99%